The impact of error and ignorance about the substance of a legal act on its invalidity(can. 126 CIC) - DZIERŻON, KS. GINTER (Prawo Kanoniczne, 2018)
In the presented article, the author’s attention has become the interpretation of can. 126 CIC regarding the influence of error and ignorance about the substance of a legal act on its invalidity. He proved that error and ignorance are autonomous flaws of a legal act. In the final part of his study, arguing against the views of WinfriedAymans and KlausMörsdorf who believed that there is a certain kind of imbalance between can. 125 §2 CIC (in which the impact of deceit and fear on the validity of a legal act was codified) and can. 126 CIC, he expressed the opinion that such a claim is unjustified. According to the author, other reasons were decisive for codifying these principles. He claims that in can. 125 §2 CIC the legislator created an option of dissolving the act because he considered that in this case the principle of justice was violated. In this way, he aimed to protect those who have been harmed. The author’s opinion is that the introduction of the principle codified in can. 126 CL was determined by other reasons, namely theoretical-legal reasons of ontological basis in the Aristotelian-Thomisticphilosophical sense. In his opinion, the distortion of the subject matter of an act in its essential elements resulting from a substantial error (ignorance) by nature cannot generate consequences other than the invalidity of a legal act.